2016
DOI: 10.1002/ejhf.524
|View full text |Cite
|
Sign up to set email alerts
|

Novel pathomechanisms of cardiomyocyte dysfunction in a model of heart failure with preserved ejection fraction

Abstract: AimsHeart failure with preserved ejection fraction (HFpEF) is increasingly common, but the underlying cellular mechanisms are not well understood. We investigated cardiomyocyte function and the role of SEA0400, an Na + /Ca 2+ exchanger (NCX) inhibitor in a rat model of chronic kidney disease (CKD) Methods and resultsMale Wistar rats were subjected to subtotal nephrectomy (NXT) or sham operation (Sham). After 8 and 24 weeks, in vivo (haemodynamics, echocardiography) and in vitro function (LV cardiomyocyte cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 27 publications
6
55
2
Order By: Relevance
“…The few studies investigating similar mechanisms in HFpEF indicate that reduced sodium-calcium exchanger function promotes slower, incomplete relaxation in this condition (13). However, we showed in a recently published study that disrupted calcium homeostasis is not a precondition for diastolic dysfunction (14).…”
Section: Pathophysiologymentioning
confidence: 65%
“…The few studies investigating similar mechanisms in HFpEF indicate that reduced sodium-calcium exchanger function promotes slower, incomplete relaxation in this condition (13). However, we showed in a recently published study that disrupted calcium homeostasis is not a precondition for diastolic dysfunction (14).…”
Section: Pathophysiologymentioning
confidence: 65%
“…Although very early in development, inhibitors of the mitochondrial sodium– calcium– (lithium) exchanger 215 , such as CGP-37157, have been shown to improve cardiac function in preclinical models of HF 216,217 . Inhibiting the sarcolemmal sodium– calcium exchanger might also be a promising approach, as demonstrated in a preclinical model of HFpEF 218 .…”
Section: Cellular/mitochondrial Ion Homeostasismentioning
confidence: 99%
“…Furthermore, patients with early stages of CKD specifically develop signs of LV diastolic dysfunction prior to the onset of clinical heart failure manifestations [18] suggesting that reduced GFR may contribute to the development of HFpEF. Although the LV abnormalities described in the present study show resemblances to those observed in rats or mice with CKD caused by 5/6 nephrectomy [19][20][21] the ACRF model may have several advantages in addition to not requiring surgery. Rats subjected to 5/6 nephrectomy typically develop only a relatively modest decrease GFR and consequently secondary metabolic changes such as alterations in mineral and bone metabolism are not as pronounced as in ACRF rats [19,[22][23][24].…”
Section: Discussionmentioning
confidence: 60%
“…Although the LV abnormalities described in the present study show resemblances to those observed in rats or mice with CKD caused by 5/6 nephrectomy [19][20][21] the ACRF model may have several advantages in addition to not requiring surgery. Rats subjected to 5/6 nephrectomy typically develop only a relatively modest decrease GFR and consequently secondary metabolic changes such as alterations in mineral and bone metabolism are not as pronounced as in ACRF rats [19,[22][23][24]. In addition, severe hypertension is a characteristic feature of most 5/6 nephrectomy models [23,25], which makes it difficult to distinguish whether cardiovascular abnormalities are primarily caused by high blood pressure or reduced kidney function.…”
Section: Discussionmentioning
confidence: 60%